Perilaku Body Shaming dan Dampak Psikologis pada Mahasiswa Kota Bogor - Resqia Indah Atsila; Imani Satriani; Yogaprasta Adinugraha (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2021)
This research was conducted in order to explain students characteristics in Bogor City, to explain body shaming that students of Bogor City have ever experinced, to explain psychological impact of body shaming, to analyze correlation between student characteristics and psychological impact of body shaming and to analyze correlation between body shaming and and psychological impact of body shaming. This research was taken place in Pakuan University, Djuanda University, University of Ibn Khaldun and Nusa Bangsa University on September until December 2019. In term of sampling techniques, this research used accidental sampling. Questionnaire and study library were used as data collecting techniques. There were there data analyze techniques, descriptive statistics, Rank Spearman and Chi-Square. The result shown that was not correlation betwen body shaming and psychological impact of body shaming